Professional identity of pre-service teachers: actual and designated identity profiles and their relationship to teacher education programs - Meyer, Dennis; Doll, Jörg; Kaiser, Gabriele (Frontiers in Education, 2023)
In this study, we investigated the professional identities of 490 preservice teachers (PSTs) at a large German university. By distributing 100 percentage points, the PSTs assessed the relevance of the roles of subject specialist (SS), didactician (DD), and pedagogue (PD) for themselves currently (actual identity) and for an ideal teacher in different school types (designated identity). A theory-based nonhierarchical cluster analysis distinguished seven profiles: three specialist profiles, three dual profiles, and one balanced profile. The distribution of the PSTs’ actual identities across these seven profiles showed expectedly large interindividual diversity. The most frequent actual identity profiles were those for which the DD and PD roles were particularly relevant (dual PD/DD profile and balanced profile). The distribution of PSTs across profiles supported the hypothesis that actual identity is related to the type of teacher education program being followed: upper secondary education PSTs were more strongly characterized by profiles that emphasized the SS role (specialized SS profile and dual SS/DD profile) than the other PSTs, and special education PSTs were more strongly characterized by profiles that emphasized the PD role (specialized PD profile and dual PD/DD and PD/SS profiles) than the other PSTs. The designated identities, on the other hand, showed greater consensus among the PSTs. The profiles that best characterized PSTs were the dual PD/DD profile and the balanced profile. In contrast, the two specialized SS and DD profiles and the dual PD/SS profile were irrelevant as designated identities. A comparison of PSTs’ actual identities with their designated identities showed that a third of the PSTs had the same profile. The diversity of professional identities and the factors in teacher training that influence them should be investigated more closely.